(untitled) (Psychology Travelogs, 2025)
The article explores the potential of a synergistic approach in the combination of psychotherapeutic methods, training technologies and family psychology in the context of growing challenges for the mental health of modern man. Synergetics as a scientific paradigm allows us to consider the psyche of an individual, his interpersonal relationships and social contexts as complex open systems capable of self-organization, adaptation and development under the influence of external and internal factors. On this basis, the feasibility of integrating various psychotherapeutic approaches, such as cognitive-behavioral therapy, body-oriented techniques, art therapy, as well as training formats (personal growth, emotional intelligence, communicative effectiveness) into a single holistic model of working with the individual is substantiated. Special attention is paid to the systemic role of the family as a key element of the psycho-emotional environment of a person: the introduction of elements of family psychotherapy into general therapeutic programs allows us to achieve a deeper and more stable result in the process of psychocorrection. Within the framework of an interdisciplinary approach, the authors combine psychological, pedagogical, sociological, neuropsychological and medical perspectives, which allows creating a multidimensional analytical framework for understanding modern mental states. Evidence is provided of the effectiveness of synergistic models in dealing with the consequences of combat stress, emotional burnout, post-traumatic states, maladjustment, in particular among military personnel, educators, medical workers and other vulnerable categories. A special emphasis is placed on the importance of training technologies as a tool not only for educational, but also for psychotherapeutic influence: trainings are considered as a form of active processing of internal resources, development of resilience, increase of communicative competence and strengthening of personal integrity. The article states that interdisciplinary interaction of specialists (psychologists, psychotherapists, teachers, social workers, doctors) is a critically necessary condition for building effective mental health support programs, especially in conditions of war, social turbulence and collective trauma. The authors emphasize that only through the combination of efforts of different branches of knowledge and practice is it possible to create flexible, adaptive and sustainable psychological models that meet the complexity of modern human needs. In this context, the synergistic approach appears not only as a methodology, but as a strategy of humanistic response to deep transformations of social reality.